The Varieties of Prudence - Gubler, Simone (Australasian journal of philosophy, 2024)
We sometimes face personal choices that are so momentous they appear to give rise to an intrapersonal analogue to the non-identity problem. Where the non-identity problem presents as a problem for morality, the intrapersonal analogue presents as a problem for prudence. The analogy has been explored recently by Das and Paul, and although, as this paper argues, their analysis fails-there is no intrapersonal analogue for the non-identity problem-it functions to highlight a persistent and perplexing puzzle for prudential rationality. This paper offers its own explanation: namely, that the phenomena that motivate the purported intrapersonal problem are better accounted for by conceiving prudence as disjunctive. To this end, I sketch a theory of two varieties of prudence.